An Improved Bit Flipping Min Sum Algorithm with Difference to Sum Ratio Factor Based on Unreliable Received Messages - Qiu, Mingchun; Zhang, Zhi; Huang, Yuzhen (Proceedings (International Conference on Communication Technology. Online), 2020)
Low density parity-check (LDPC) codes is known for its outstanding performance near the Shannon limit. In this paper, an improved min sum algorithm with difference to sum ratio factor (DSR-MS) is proposed, which is called bit flipping min sum algorithm with DSR factor based on unreliable received messages (DSR-URMBFMS). It belongs to the hybrid decision decoding scheme. A novel assistant stage associated with the bit flipping (BF) algorithm is introduced after each failed iteration of DSR-MS, and the sequence with minimum sum of syndrome vector (SSV) is taken as the final decoding output. Simulation results show that the proposed algorithm achieves faster convergence rate and better performance than the DSR-MS algorithm.